The Sundanese Muslim Perceptions toward Reciting Quran in Debus Art Show - Setiadi, Yadi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2023)
The Qur'an is the word of Allah, the Lord of the universe, so in history the Prophet Muhammad often gave examples of various miracles that arose after reading verses or letters from the Koran, the most popular of which were as a medicine for healing health, an antidote to magic, and therapy for mental illness. In this regard, the Muslim community in Indonesia, especially the Sundanese, has practiced the Koran a lot in various aspects of life, one of which is in performing immune arts. For the Sundanese Muslim community, reading the verses of the Koran can give birth to confidence in the heart, so that they feel safe from all evil and believe themselves to be immune from firearms and sharp weapons. Based on this phenomenon, this research was conducted to see the views or beliefs of the Sundanese Muslim community in Indonesia, regarding the practice of the verses of the Koran in the art of immunity. To explain these objectives, a qualitative field study was conducted. In addition, the disclosure used ethnographic methods, namely collecting research data from research subjects based on cultural/ethnic perspectives. Research data obtained through observation techniques, interviews and documentation. The results of the study show that the perception of the Sundanese Muslim community towards the use of verses of the Koran in performing arts of immunity is a belief in faith. By reading the verses of the Koran, one is actually asking Allah, the Lord of the universe, for safety, protection, security, and strength and to be avoided from all bad things/accidents. In other words, reading the verses of the Koran in the debus art is a belief in the faith in the creator of the universe for help and protection, so that we are kept away from bad things.